Indonesia Dampak Tayangan Talkshow Televisi Indonesia Lawyers Club (ILC) Terhadap Mahasiswa : (Survei Terhadap Mahasiswa Fakultas Ilmu Komunikasi dan Bahasa UBSI Margonda Depok) - Fauziah Muslimah; Eni Saeni (LPPM Universitas Bina Sarana Informatika, 2020)
The world of television broadcasting is a world of creativity. The tight competition in the television industry requires television station managers to devote brilliant ideas and ideas to maximize their creative and innovative power in producing broadcast programs. Television stations, especially commercial television, will go out of business, go bankrupt, if they fail to produce and choose programs that are attractive to the audience. The main difficulty for television station program managers is determining whether a program will reach a large audience. One of the television programs that the audience is interested in is a talk show. One of the talk show programs that can be said is phenomenal, namely